EFFECT OF EARLY MOBILIZATION ON CHANGE OF PAIN LEVEL IN PATIENTS POST APPENDICTOMY OPERATION AT SURGERY ROOM OF RSUD dr. ABDUL AZIS SINGKAWANG YEAR 2019 - Tri Nova Aprianti; Usman Seri; Saliana Zaini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Post appendectomy patients need maximum care to speed up the recovery of bodily functions. Matters relating to the care of postoperative patients and carried out immediately after surgery include doing early mobilization exercises. Early mobilization exercises can improve blood circulation which will trigger pain reduction and faster wound healing. Through this mechanism, early mobilization is effective in reducing the intensity of postoperative pain. The purpose of this study was to determine the effect of early mobilization on changes in pain levels of post operative appendectomy patients in the operating room of RSUD dr. Abdul Aziz Singkawang. The research method used is quantitative research with quasy experimental research design. The approach method uses a pre and post control group design research study. Data analysis using statistical test dependent t-test The sampling technique in the form of consecutive sampling in post operative appendectomy patients with a sample of 16 respondents. The instruments used were pain level questionnaire and early mobilization observation sheet. The results of the study are p value of 0.001 with a significance value of 0.05. So, p value 0.05. There is an influence of early mobilization on changes in pain levels of post operative appendectomy patients in the Operating Room of RSUD dr. Abdul Azis Singkawang. Saan for the nurse profession to provide an explanation of the importance of mobilization and provide early mobilization exercises to post operative appendectomy patients in accordance with procedures as permanent activities in an effort to prevent loss of bodily functions so as to improve the quality and quality of service.